Energy Evolution Law of Marble Failure Process Under Different Confining Pressures Based on Particle Discrete Element Method - Yang, Yan-Shuang; Cheng, Wei; Zhang, Zhan-Rong; Tian, Hao-Yuan; Li, Kai-Yue; Huang, Cai-Ping (Frontiers in Materials, 2021)
The energy dissipation usually occurs during rock failure, which can demonstrate the meso failure process of rock in a relatively accurate way. Based on the results of conventional triaxial compression experiments on the Jinping marble, a numerical biaxial compression model was established by PFC2D to observe the development of the micro-cracks and energy evolution during the test, and then the laws of crack propagation, energy dissipation and damage evolution were analyzed. The numerical simulation results indicate that both the crack number and the total energy dissipated during the loading process increase with confining pressures, which is basically consistent with the experiment results. Two damage variables were presented in terms of the density from other researchers’ results and energy dissipation from numerical simulation, respectively. The energy-based damage variable varies with axial strain in the shape of “S”, and approaches 1 more closely than that based on density at the final failure period. The research in the rock failure from the perspective of energy may further understand the mechanical behavior of rocks.